Assessing the Relationship between Entrepreneurial Resources and Competencies Controlling for Entrepreneurial Improvisation in Select Micro and Small Businesses - Gutierrez, Ernell B.; Alberto, Eden U.; Chang, Edgar L.; Jucom, Jayson C.; Marticio, Ramon L. (Future Science / FSH-PH Publications, 2025)
Sustaining resources has been a challenge for businesses, particularly those highly dependent on raw materials derived from the natural environment. The roles of competencies and improvisation are crucial in adapting to and sustaining entrepreneurial activities, including, but not limited to, production, sourcing, and operations. Thus, this research is conducted to determine and assess the extent of entrepreneurial resources, entrepreneurial competencies, and entrepreneurial improvisation among select micro and small businesses. The research is descriptive and correlational in nature. The simple mean is used to assess the extent of entrepreneurial practices in terms of Resources, Competencies, and Improvisation, while Partial Correlation is used in determining the relationship between resources and competencies while controlling for business improvisation. Results revealed that for Entrepreneurial Resources, the select businesses agreed on the importance of resources with respect to entrepreneurial activities, specifically for Financial, Human, Physical, and Environmental. At the same time, Strong Agreement is expressed on Entrepreneurial Competencies, specifically for Systematic Planning and Monitoring, Opportunity Seeking, Goal Setting, and Persuasion and Networking. Lastly, a Strongly Agree is also expressed on Improvisation specifically for Ingenuity and Adaptability. Entrepreneurship requires various factors that contribute to its success and sustainability, such as Resources, competencies, and the ability to improvise, which must be present in all entrepreneurial activities. With regards to the relationship between Entrepreneurial Resources and Competencies when controlled by Entrepreneurial Improvisation, the results revealed a significant and strong positive relationship.